Chinch-bug - Evans, Jephthah W. (My University, 1894)
Introduction: Introduction: Were you to ask the western fruit grower which insect in most injurious to his efforts, he would undoubtedly answer ‘the Curculio’. Were you to confront the western grain grower with this same question, he would certainly answer ‘the Chinch-bug’. And he would be right. The Hessian Fly, often simply called ‘The Fly’, injures the wheat by its larva or maggot living between the sheath and the stems and thus absorbing the sap before it reaches the fruiting portion. The ‘Weevil’ in certain favorable seasons does considerable damage by its little orange-colored, legless larva sucking the sap from the growing kernel. The ‘Joint-worm’ may at times assist in allaying the growth of the plant by causing abnormal enlargements of the joints. The ‘Plant-louse’, the ‘White-gnat’, the ‘Wire-worm’, and certain ‘Cut-worms’ each have a tendency to lessen the return of the western gran grower, but the combined effort of all these does not equal the damage done by the chinch-bug. He is undoubtedly the meanest insect the western farmer has to deal with.
Citation: Evans, Jephthah W. Chinch-bug. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Entomology; Wheat; Chinch bug; Pests; Theses; Manuscripts (documents)